2015
DOI: 10.1080/19942060.2015.1031318
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating wave forces on groups of three and nine cylinders using a 3D numerical wave tank

Abstract: The evaluation of the complex wave regime due to wave interaction with a large group of cylinders placed in proximity requires an efficient and accurate numerical model. This paper presents the application of a two-phase Computational Fluid Dynamics (CFD) model to carry out a detailed investigation of wave forces and flow around vertical circular cylinders placed in groups of different configurations at low Keulegan-Carpenter (KC) numbers. The 3D numerical wave tank is validated by comparing the numerical resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…More recently, Kamath et al (2015aKamath et al ( , 2015b reported CFD results of wave interaction with multiple vertical cylinders. They performed simulations using a k-ω turbulence model and observed unphysical wave damping based on RANS turbulence modelling.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Kamath et al (2015aKamath et al ( , 2015b reported CFD results of wave interaction with multiple vertical cylinders. They performed simulations using a k-ω turbulence model and observed unphysical wave damping based on RANS turbulence modelling.…”
Section: Introductionmentioning
confidence: 99%
“…The numerical wave tank is validated for wave generation and propagation for waves of high and low steepnesses [13] [26] [14] and for the computation of wave forces [27]. The following sections present the results for wave forces evaluated for a single cylinder and linear arrays of two, three, four and five cylinders of diameter D = 0.5 m in a water depth d = 0.5 with incident waves of wavelength L = 2.0 m for heights H = 0.006 m (linear wave theory) and H = 0.15 m (5th-order Stokes wave theory).…”
Section: Resultsmentioning
confidence: 99%
“…The mooring model is implemented in the open-source CFD code REEF3D [8]. The model has been used and validated for a wide range of marine applications, such as breaking wave kinematics [9], breaking wave forces [10] and sloshing [11]. For floating bodies, an extension of the local directional immersed boundary method [12] using the field extension method [13] is implemented.…”
Section: Omae2018-77776mentioning
confidence: 99%